Diagnostic tests in urology: percentage of free prostate‐specific antigen (PSA). (29th October 2012) - Yi, Yooni; Breau, Rodney H.; Witiuk, Kelsey; Neuberger, Molly M.; Dahm, Philipp
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Free to total PSA ratios are commonly used as an adjunct to total PSA levels to better define an individual's risk for prostate cancer; however, its strengths and weaknesses are not well understood. This article illustrates the use of likelihood ratios that can be generated from the reported sensitivities and specificities from given free to total PSA thresholds in either increasing or decreasing an individual patient's probability of prostate cancer. Understanding the strengths and limitations of free to total PSA testing will help clinicians anticipate whether its use is indicated or not.